2005
DOI: 10.1016/j.jasms.2004.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Electron capture dissociation of polypeptides in a three-dimensional quadrupole ion trap: Implementation and first results

Abstract: The adverse influence of the radio frequency (RF) voltage on electrons has been the main obstacle for the implementation of electron capture dissociation (ECD) in three-dimensional quadrupole ion traps (3D QITs). Here we demonstrate that the use of axial magnetic field, together with the injection of low-energy (<5 eV) electrons, in the beginning of the positive RF semi-period achieves trapping of electrons for a period of time comparable with the semi-period duration. Importantly, the energy of the electrons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
72
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 9 publications
0
72
0
Order By: Relevance
“…The analytical power of ECD in FT-ICR MS encouraged researchers to develop alternative methods for lower resolution mass spectrometers. As a result, ECD and ion-ion reaction based electron-transfer dissociation (EID) have been implemented and developed into efficient tools in linear and Paul radiofrequency ion traps [6][7][8][9][10] as well as in a digital ion trap [11]. ECD/EID implementation in radiofrequency devices that typically constitute the first stage of a hybrid mass spectrometer allows for subsequent high-resolution detection of product ions with FT-ICR, Orbitrap [12], or time-of-flight (TOF) [13] mass analyzers.…”
mentioning
confidence: 99%
“…The analytical power of ECD in FT-ICR MS encouraged researchers to develop alternative methods for lower resolution mass spectrometers. As a result, ECD and ion-ion reaction based electron-transfer dissociation (EID) have been implemented and developed into efficient tools in linear and Paul radiofrequency ion traps [6][7][8][9][10] as well as in a digital ion trap [11]. ECD/EID implementation in radiofrequency devices that typically constitute the first stage of a hybrid mass spectrometer allows for subsequent high-resolution detection of product ions with FT-ICR, Orbitrap [12], or time-of-flight (TOF) [13] mass analyzers.…”
mentioning
confidence: 99%
“…9 Unfortunately, ECD is largely limited to FT-ICR mass spectrometers, and other types of mass spectrometers are not well suited for the technique, although there have been some recent reports of efforts to adapt electrodynamic ion traps for ECD. 10,11 While the trapping of electrons and peptide/protein cations simultaneously is difficult in electrodynamic ion traps, cations and anions can be stored together readily, 12 and it has recently been reported that ion/ion reactions can provide a way to access ECD-like results in electrodynamic ion traps. Hunt and co-workers have reported results for some anionic reagents that react with peptide cations by electron transfer, producing ECD-like fragmentation to yield c-type and z-type sequence ions in a process termed electron-transfer dissociation (ETD).…”
mentioning
confidence: 99%
“…156,157 More recently, efforts have been made to develop a quadrupole ion trap capable of performing ECD experiments. 158,159 Since the first application of ECD to the characterization of peptides and proteins, 160 the combination of high resolving power FT-ICR with ECD and other activation methods has been successfully applied to de novo protein sequencing 148,154,161 -163 and the location of labile post-translational modifications in polypeptides and proteins. 153,164 -166 Fig.…”
mentioning
confidence: 99%